Distribution and phylogenetic relationships of native and introduced pit scales (Hemiptera: Coccoidea: Asterolecaniidae) in North and South America (Bollettino di zoologia agraria e bachicoltura, 2024)
The pit scales or Asterolecaniidae represent a diverse group found in all major biogeographic regions of the world on a variety of host plants. Specimens representing both known and unknown species were obtained from institutions in North and South America for study. Species were described and illustrated based on morphological characters of the adult females. This study assessed the morphological characters for 48 of the 64 species of pit scales found in North and South America representing the genera Asterodiaspis, Asterolecanium, Bambusaspis, Neoasterodiaspis, Palmaspis, Planchonia, and Russellaspis. Because of the presence of recent descriptions, eight species of Grammococcus and Palmaspis were not described, but were included in a systematic key in addition to 11 new species (two species of Asterolecanium, five species of Bambusaspis, and four species of Palmaspis). Also, three species in the genus Bambusaspis were synonyrnized and the genus Grammococcus was included in the subfamily Asterolecaniinae. Computer-generated phylogenetic trees were developed and tested for robustness. The phylogenetic relationships of 38 species in the subfarnily Asterolecaniinae were evaluated based on 43 morphological characters of the adult females. A complete consensus tree of the 40 most parsimonious trees was developed. This study suggests that most genera may be monophyletic, while the genera Asterolecanium and Palmaspis appear to be paraphyletic. Pit scale biodiversity has not been adequately investigated, and many additional discoveries of new species are expected from tropical regions.
Keywords: pit scales; Asterolecanium; phylogenetic analysis; scale insects